Vibration-based damage identification in composite plates using 3D-DIC and wavelet analysis. (1st July 2022) - Sun, Guangyong; Wang, Yuansong; Luo, Quantian; Li, Qing
Graphical abstract: Highlights: Full-field vibration measurement of CFRP plates by digital image correlation (DIC). Baseline-free damage detection based upon mode shapes derived from DIC data. Wavelet analysis of mode shapes to identify damage location, size and shape. Influence of measurement DOFs on damage detection effect and efficiency is revealed. Abstract: High-speed three-dimensional digital image correlation (3D-DIC) techniques can acquire full-field vibration responses under a single excitation, which is not restricted by the number of degrees of freedom (DOFs) in measurement compared with accelerometers and laser Doppler vibrometers (LDVs). Therefore, 3D-DIC exhibits compelling capacity in dynamic testing, especially for nondestructive damage detection. Based on experimental modal analysis (EMA), this study presents a damage detection method without using a baseline model, which combines the advantages of 3D-DIC with two-dimensional continuous wavelet transform (2D-CWT) for damage detection and recognition. The carbon fiber reinforced plastic (CFRP) composite plates with prefabricated artificial damages, including spatial notches and local crack, were investigated. The mode shapes of damaged CFRP composite plates were obtained by singular value decomposition (SVD) from the matrix of frequency response functions (FRFs). Then the mode shapes were analyzed by using wavelet transform, and the damage index was derived from the wavelet coefficients. For comparison, two other damage indices, namely mode shape curvature and polynomial fitting difference, were also derived. It is found that 3D-DIC could provide different measurement DOFs in line with the damage form for post-processing; and the Mexican-hat wavelet analysis can accurately detect the location and size of damage by suppressing the effects of measurement noise.